Counting what counts: Moral considerations and market surplus - Paul Koster (Tinbergen Institute, 2023)
Public benefit-cost analysis of market policies often relies on a particular definition of market surplus that adds up consumer and producer surplus and external costs. This paper provides an overview of conceptual strategies to deal with moral considerations and then develops an adjusted market surplus function that is able to deal with heterogeneous normative perspectives. In a stylised model, new expressions for first-best Pigouvian taxes are developed that depend on moral considerations. A novel moral rule-of-half approximation is provided for the potential surplus gains of taxation or behavioural change.
Keywords: D04; D61; D62; D63; B59; A13; 330; Welfare economics; Moral considerations; Normative Pluralism; Ethics and market value; Benefit-cost analysis; Pigouvian taxation.